Investigation on folkloric medicines in Badwani district (M.P.) India - Patil ³, P. S. Patil¹*, Patil M.V.²; D. A. (Current Botany, 2011)
The paper communicates first-hand information on 25 plant species belonging to 25 genera and 21 families traditionally used by the aborigines and rural populace of Badwani district (Madhya Pradesh, India) to treat various human diseases.Of these, 16 species are being reported for the first time from India. These are administered to various diseases such as dysentery, whitlow, throat infection, mouth ulcers, earache, impotency, fever, bone-fever, cough, migraine, stomach-ache, bone fracture, rheumatism, post-pregnancy complaints, etc., They are employed in the form of extract, infusion, paste, powder, juice, decoction, etc. The district is inhabited by tribes viz., Gond, Baiga, Koraku, Bhariaya, Halba, Bhil, Kaul and Pawara. The population of the region is predominantly rural and tribal having considerable knowledge about ambient plant wealth and their traditional utilities. The correct scientific name of plant, family and local names, preparations of medicinal recipes, dosage, mode of administration and diseases treated are given. These have been gathered from medicine-men, elders and experienced informants. This is attempt to evaluate the ethnomedicinal claims, which in turn on further scientific scrutiny, may emerge as new drugs. Ã‚Â